Mempertimbangkan Euritmika Emile Jaques-Dalcroze pada Pengajaran Seni Musik Anak Usia Dini - Sri Utomo, Muhammad Ridhlo al-Qodri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2015)
Emile Jacques Dalcroze acquires a fame in developing the of music for children as the founder of theory of Eurythmics, a system of training through physical movement to music. This article is intended to discuss the theory of eurythmics as well as how to adapt such theory in the teaching of music for preschool students in Indonesia.